Impacts on the World of Work - Burns, Robert B (My University, 2023)
Home The Human Impact of the COVID-19 Pandemic Chapter Impacts on the World of Work Robert B. Burns Chapter First Online: 17 July 2023 4 Accesses Abstract The crucial issues of this chapter focus on the way Covid has affected unemployment levels, where work is conducted, and what personal benefits employees seek from work now. Restrictions imposed by national governments in developed countries involving quarantine periods, drastically reduced travel limitations, social distancing, mask wearing, limitations on numbers gathering together, all conspired to limit work opportunities and consumer ability to seek purchases, leading to economic slowdown with minimal activity for, and even closure of, many businesses. Hence, unemployment surged and many employees, where feasible, worked from home. The pros and cons of work from home (WFH), including the employee preference for continuation in the hybrid form, are reviewed along with discussion of the ‘Zoom’ effect. Employees are showing increasing propensity to move from their preCovid employment and seeking either more WFH, or to be entrepreneurial or joining more caring companies that have employee wellbeing more central in their philosophy. The pandemic has changed the priory rankings of reasons why people work with money less salient while intrinsic motivations like achievement, self-esteem, personal satisfaction and better life-work balance in a flexible system will contribute more significantly in the future.
The Human Impact of the COVID-19 Pandemic
Keywords: Labour market